Two Late Quaternary Pollen Records from South-Central Alaska - Anderson, P.; Lozhkin, A.; Eisner, W.; Kozhevnikova, M.; Hopkins, D.; Brubaker, L.; Colinvaux, P. (Géographie physique et Quaternaire, 1994)
ABSTRACTPollen records from Wonder and Ten Mile lakes, located at aititudinal treeline to the north and south of the Alaska Range respectively, document the vegetation history of a portion of the southern Alaskan boreal forest. The new pollen diagrams indicate a Betula shrub tundra, preceded at Wonder Lake by a sparse herb tundra, which characterized these two areas during latest Wisconsinan times. Populus was in the vicinity of Ten Mile Lake ca. 10,000 BP, but was apparently absent from Wonder Lake. Picea glauca grew at or near Ten Mile Lake by 9100 BP, with P. mariana becoming important ca. 7000 BP. The first forests at Wonder Lake were also dominated by P. glauca and followed by increased numbers of P. mariana. The timing of forest establishment at Wonder Lake is uncertain due to problematic radiocarbon dates. Alnus appears to be common in both regions by ca. 7000 BP. These records suggest that paleo-vegetational reconstructions are more difficult for the southern than northern boreal forests in Alaska because of greater topographic diversity, difficulties with over-representation of some pollen taxa, and problems with radiocarbon dating. Despite these concerns, available data from south-central Alaska suggest that southern and northern forests differ in their vegetational histories. Such differences, when related to temperature fluctuations that have been postulated for the Holocene, imply that the Alaskan boreal forest may not respond uniformly to future global warming.